Exploring the interplay of cultural capital, habitus, and field in the life histories of two West African teacher candidates. Issue 5 (19th October 2016) - Park, Gloria; Rinke, Carol; Mawhinney, Lynnette
Abstract : This paper captures the life histories of two West African pre-service teachers pursuing their education in the United States. Based on a larger study examining the life histories of 45 undergraduate pre-service teachers, these narratives focus specifically on international student experiences in the US. Grounded in Bourdieu's theory of habitus, capital, and field, the life histories of Bakar and Selma illustrate how their capital and habitus become contingent on the field(s) (i.e. sites, time, and agents within a specific context) in which they are situated. The narratives of Bakar and Selma captured their early educational experiences, teacher preparation practices, and future possibilities as they moved in and out of different fields where the exchange of capital occurred, which then led to restructuring and/or de-valuerization of certain habitus . The experiences of Bakar and Selma heighten our awareness of the capital and habitus deployed in a variety of contexts – fields – in the US and elsewhere. We conclude by incorporating discussion focused on working with international teacher candidates.